Productizing a mobile application: participatory design and development - Oliveira, Leonardo Rafael Miranda (2019)
The advent of smartphones changed the way we communicate and collaborate. During the last years mobile applications have experienced an exponential growth, representing new technological challenges that require effective solutions. The internet has plenty of information about building applications, but many aspects are ignored or simplified to present a simple solution to who is starting. The construction of a prototype is relatively straightforward, but there are several challenges faced when building an application with higher standards. Considering the target audience, does it meet the user needs? Is it easy to use? Knowing that it can potentially be downloaded by a growing number of users, is it scalable? What is the right deployment? How to handle frequent updates? These are some of the questions that nourished the research agenda in this dissertation. It starts from an idea for a mobile application and goes through some of the aspects to consider when conceiving and transforming that application in a product ready to be delivered to the customers, available in the Google Play Store or Apple App Store. Thus, this document reports on all the steps that were followed during this project, regarding aspects mainly related to the design, development and deployment stages. The beta version of the app is currently available in the Play Store, with more than 300 users registered. It is expected that the application is sufficiently representative of the challenges it involves, so the co-design and development process could be adapted to other applications. Hopefully, the ideas discussed here can be an example of what might be the problems to keep in mind when starting to develop an application, what might be the solutions for these problems and what will be the mistakes to avoid. The future work includes the necessary improvements to reach the version 1.0 and the further exploration of some topics, such as gamification and A/B testing to improve the user interface and optimize the user experience.